BRAND “BALI SHANTI” PADA MEDIA PROMOSI PARIWISATA PEMERINTAH INDONESIA DI PARIS - Erinda Putri Moniaga, Natasha (Jurnal Master Pariwisata (JUMPA); Volume 01, Nomor 02, Januari 2015, 2015)
This study examines promotional print media on Bali in form of pamphlet and folder made by the Embassy of the Republic of Indonesia to Paris and the Ministry of Tourism and Creative Economy of the Republic of Indonesia. The aims were to recognize the messages conveyed by both medias and whether the meaning of Bali’s branding, Bali Shanti (Bali Peace), could be delivered or not. The method used in this research were discourse analysis with semiotical approach, and Barthes’s semiotics theory was used as primary theory. The message of Bali Shanti brand is about peace and harmony, since this brand was created to restore the image of the island of Gods after the Bali Bombing in 2002 and 2005. After the analysis, it was found that the pamphlet conveyed to the readers that Bali is a peaceful island with unique culture based on Balinese Hindu religion, thus, this media could transmit the message of Bali Shanti. Meanwhile, the folder expressed Bali as an island with lots of beautiful nature destinations and has exceptional culture, but the message of Bali Shanti brand could not be delivered to the audience.